CIVIC EDUCATION OF YOUTH IN THE CONDITIONS OF THE EURASIAN INTEGRATION OF RUSSIAN SOCIETY (EDUCATION IN THE 21ST CENTURY, 2023)
The modern pedagogical process is designed to ensure the formation of diversified, morally and socially responsible citizens who can make decisions in a situation of choice, predicting possible consequences, ready for democratic cooperation and intercultural interaction, capable of participating in the development of the economic, political and cultural spheres of Russian society. At the present stage of the Eurasian integration processes and political transformation of Russia, the problem of the formation of civic culture and civic education play a civiliarchic role. The transition of Russian society from one political regime to another and the change in values are a factor in changing the attitude of society towards citizenship. Citizenship has always played an important role in the political consciousness of Russia, and in the context of the modern transformation of society, this fact cannot be underestimated. The civilizational character of Russian federalism and the civic dimension of nationality are specific, and one of the features of this character is citizenship.
Keywords: Citizenship, civic education, civiliarchic values, youth, political socialization, Russia, Eurasian integration.